An outbreak of salmonellosis in chicks ( Gallus gallus) by Salmonella paratyphi C - Xavier, Vicente Leite; Brada, Wilherlm; Langenegger, Charlotte Hubinger (Pesquisa Agropecuaria Brasileira, 2014)
An outbreak of salmonellosis (paratyphoid) in Gallus gallus (chicks), is reported. The etiological agent was found to be Salmonella paratyphi C (6, 7, Vi: c: 1, 5). This Salmonella type was isolated from the heart blood, internal organs and bone marrow of six chicks, that were weeks to one month old. They were raised at a ranch located in Itaguaí, State of Rio de Janeiro, Brazil, in the "Baixada Fluminense". The main infection symptoms were diarrhea, loss of appetite, and listlessness. Post mortem examination revealed generalized septicemic lesions, punctate hemorrhages on the sub-epicardic region, lungs and liver, and true hemorrhagic suffusions especially in the intestines. Some small necrotic areas could be seen in the liver, spleen and gizzard wall. Every bird examined showed a congested and enlarged spleen. From the onset to death, the disease lasted from four to seven days and the death rate was about 20%. It is the first time this disease is registered in domesticated birds in Brazil.